Link adaptation for LTE-A systems employing MMSE turbo equalization - Cheema, Sher Ali; Grossmann, Marcus; Landmann, Markus; Del Galdo, Giovanni (WSA 2014; 18th International ITG Workshop on Smart Antennas, 2014)
Turbo equalization for multiple-input-multipleoutput (MIMO) wireless communication systems can achieve close-to-optimal performance over frequency selective channels at reasonable complexity. In this paper, a turbo equalizer for the Long Term Evolution-Advanced (LTE-A) uplink is proposed. Moreover, a novel approach for link adaption based on the extrinsic information transfer (EXIT) chart analysis of the turbo equalizer is discussed. Specifically, it is shown that the specific feedback parameters CQI, PMI, and RI used for spatial processing can be efficiently calculated. Numerical results are presented to demonstrate the performance enhancement achieved in realistic channel fading environments by the proposed link adaption scheme.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Channel Quality Indicator (CQI); Long Term Evolution-Advanced (LTE-A); Multiple-Inputs Multiple-Outputs (MIMO); Precoding Matrix Indicator (PMI); Rank Indicator (RI)